2012
DOI: 10.1021/jf3008647
|View full text |Cite
|
Sign up to set email alerts
|

NMR-Based Metabolic Profiling of Rice Wines by F2-Selective Total Correlation Spectra

Abstract: In this study, we performed NMR-based metabolic profiling of major rice wines (Japanese sake, Chinese Shaoxing wine, and Korean makgeolli). In the (1)H NMR spectra, the rice wines showed broad resonances in the region of about 7.9-9.0 ppm. These resonances showed many and complex correlations with approximately 0.5-4.5 ppm in the F(2)-selective TOCSY (total correlation spectroscopy) spectra, and these correlations were attributed mainly to peptides. These spectral patterns were characteristic of individual ric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 29 publications
1
17
0
Order By: Relevance
“…For the assignment of unreported signals, we predicted candidate compounds using the Biological Magnetic Resonance Bank (BMRB) 46 . Finally, we confirmed that the signals were correctly assigned to the candidate compounds using 2D NMR spectra and spiking experiments 21 . The integral value of each signal was calculated using ACD/NMR Workbook Suite V2012.…”
Section: Methodssupporting
confidence: 64%
“…For the assignment of unreported signals, we predicted candidate compounds using the Biological Magnetic Resonance Bank (BMRB) 46 . Finally, we confirmed that the signals were correctly assigned to the candidate compounds using 2D NMR spectra and spiking experiments 21 . The integral value of each signal was calculated using ACD/NMR Workbook Suite V2012.…”
Section: Methodssupporting
confidence: 64%
“…Four separate In Figure 4 one sees that the hexane extract does not provide useful chemical information between 10.0-6.5 ppm as might be expected since it does not tend to extract nonpolar metabolites. However, the spectra obtained from the pure ethanol extract had many peaks in this range and also at higher field, such as those of trigonelline, at 8.75, 8.87 and 9.22 ppm, 59,60 guanosine at 8.00 ppm, 54,61 the region for the chlorogenic acids at 7.8-6.1 ppm, 62 theogallin at 7.08 ppm, 63 α-glucose at 5.20 ppm, 60,64 β-glucose at 4.61 ppm, 60,64 malic acid at 4.33 ppm, 64 serine at 4.08 ppm, 65 quinic acid at 3.56 ppm, 63 choline at 3.20 ppm, 59,60 succinic acid at 2.54 ppm, 52,64 glutamine at 2.16 ppm, 60,64 acetic acid at 1.90 ppm, 52,59 alanine at 1.52 ppm, 59,60,64 pigment methyl groups at 1.21 ppm [46][47][48][49] and valine, leucine and isoleucine at 1.08-0.70 ppm. 54,60,61 In Figure 4, on the other hand, the hexane extract exhibits strong peaks at 5.65 and 5.3 ppm characteristic of the -CH=CH-R structure in fatty acid chains.…”
Section: Resultsmentioning
confidence: 99%
“…The score values indicate that negative peaks correspond to the irrigated extracts whereas positive ones indicate metabolite peaks predominant in the unirrigated extracts. The peaks at 1.34 ppm characteristic of lactate, 67 at 1.65 ppm of arginine 60 and at 3.88 ppm of methionine 61 are more intense in the leaf extracts of the unirrigated plants, while those at 1.30, 3.20, 3.34 and 3.86 ppm assigned for threonine, 65 choline, 52 proline 60 and serine, 65 respectively, are higher in irrigated leaf extracts, indicating the higher abundances of these metabolites in the two typologies of samples.…”
Section: Resultsmentioning
confidence: 99%
“…In some situations where a narrow chemical shift region is to be studied, band‐selective homodecoupling methods or homonuclear band selective method is favorable. Band‐selective NMR experiments (i.e., F 2 ‐selective TOCSY) have been applied for the measurement of a single specific region and to identify low abundant metabolites for the quantification of trace components in complex matrix, and for metabolic discrimination of mango juice from various cultivars, and rice wines . 1D band‐selective TOCSY has been reported for removing the integral background from unresolved peaks and thereby to improve the result of subpopulation cluster resolution in human urine samples …”
Section: Introductionmentioning
confidence: 99%
“…Band-selective NMR experiments (i.e., F 2 -selective TOCSY) have been applied for the measurement of a single specific region and to identify low abundant metabolites for the quantification of trace components in complex matrix, [46] and for metabolic discrimination of mango juice from various cultivars, [47] and rice wines. [48] 1D band-selective TOCSY has been reported for removing the integral background from unresolved peaks and thereby to improve the result of subpopulation cluster resolution in human urine samples. [49] TOCSY NMR based web server database [50][51][52] is also proposed for correlation of chemical shift information of the signals in a given spin system of known and unknown molecules in complex mixtures.…”
Section: Introductionmentioning
confidence: 99%